Spartina alterniflora has the highest methane emissions in a St. Lawrence estuary salt marsh. (30th August 2022) - Comer-Warner, Sophie A; Ullah, Sami; Ampuero Reyes, Wendy; Krause, Stefan; Chmura, Gail L
Abstract: Salt marshes have the ability to store large amounts of 'blue carbon', potentially mitigating some of the effects of climate change. Salt marsh carbon storage may be partially offset by emissions of CH4, a highly potent greenhouse gas. Sea level rise and invasive vegetation may cause shifts between different elevation and vegetation zones in salt marsh ecosystems. Elevation zones have distinct soil properties, plant traits and rhizosphere characteristics, which affect CH4 fluxes. We investigated differences in CH4 emissions between four elevation zones (mudflat, Spartina alterniflora, Spartina patens and invasive Phragmites australis ) typical of salt marshes in the northern Northwest Atlantic. CH4 emissions were significantly higher from the S. alterniflora zone (17.7 ± 9.7 mg C m −2 h −1 ) compared to the other three zones, where emissions were negligible (<0.3 mg C m −2 h −1 ). These emissions were high for salt marshes and were similar to those typically found in oligohaline marshes with lower salinities. CH4 fluxes were significantly correlated with soil properties (salinity, water table depth, bulk density and temperature), plant traits (rhizome volume and biomass, root volume and dead biomass volume all at 0–15 cm) and CO2 fluxes. The relationships between CH4 emissions, and rhizome and root volume suggest that the aerenchyma tissues in these plants may be a major transport mechanism of CH4 from anoxic soils to the atmosphere. This may have major implications for the mitigation potential carbon sink from salt marshes globally, especially as S. alterniflora is widespread. This study shows CH4 fluxes can vary over orders of magnitude from different vegetation in the same system, therefore, specific emissions factors may need to be used in future climate models and for more accurate carbon budgeting depending on vegetation type.